"مسلك واختيارات الإمام أبي داود بن نجاح في الرسم القرآني من خلال كتابه مختصر التبيين لهجاء التنزيل من أول سورة الكهف إلى خاتمة سورة المؤمنون-" - قدة, سعد (University of Eloued جامعة الوادي, 2018)
"ملخص الدراسة تناولت في هذه الرسالة: ""مسلك واختيارات الإمام أبي داود سليمان بن نجاح في الرسم القرآني من خلال كتابه مختصر التبيين لهجاء التنزيل -من أول سورة الكهف إلى نهاية سورة المؤمنون-"". وتتكون خطة الدراسة من مقدمة، وثلاثة مباحث، وخاتمة، وفهارس. المبحث الأول: يتعلق بترجمة موجزة لشخصية الإمام أبي داود ومصنفه المختصر، حيث أبان البحث عن أهم مراحل حياته، وأبرز مكانته العلمية، وأوضح مسلك الذي سار فيه في تأليف كتابه المختصر. أمّا المبحث الثاني: وجاءت الدراسة فيه متعلقة ببعض المفاهيم التي لها صلة بالرسم القرآني والموضوع ككل، فأبنت عن تعريف الرسم القرآني وقواعده، وكذا أهم مصادر هذا العلم. أمّا المبحث الثالث: فقد عُني باختيارات الأمام أبي داود في الرسم القرآني من أول سورة الكهف إلى آخر سورة المؤمنون. وقد أبانت الدراسة قوة اختيارات هذا الإمام، وأنه لم يكن مقلداً في اختياراته العلمية بل كان مجتهداً يعتمد على الدليل. وحوت خاتمة البحث أهم النتائج والتوصيات المستخلصة من الدراسة. ثم ختمت الدراسة بفهارس فنية كاشفة عن مضامين الرسالة. *** والحمد لله على توفيقه وامتنانه *** " "Abstract This dissertation has dealt with ""the course and the choices of the imam Abi Dawid Sulayman Ibn Najah"" in the quraanic drawing through his book "" Mukhtasar al-tabyin lhija al-tanzil "" from the beginning of ""surah al- kahf "" till the end of "" surah al- Mu'minun "". The study consists of an introduction, three sub – chapters, a conclusion and a bibliography . The first sub – chapter concerns a brief presentation of the personality of Abi Dawid and his concise book.The research has shown the major stages of his life and has featured his scientific status . It has explained the course that he followed in the compilation of his concise book. The second sub- chapter of the study concerns some concepts that are linked to the quraanic drawing and the whole subject. It has shown the definition of the quraanic drawing , its basics , and the major sources of the science. The third sub-chapter concerns the choices of the imam Abi Dawid in the quraanic drawing from the beginning of ""surah al-kahf "" till the end of "" surah al- mu'minun "". The study has revealed the strength of the choices of the imam, and the fact that he was not imitative in his choices ,but he was hard – working relying only on scientific evidence. The conclusion contains the main results and the recommendations extracted from the study. It has been concluded by an artistic cited- works revealing the content of the dissertation. Praise to Allah for his kindness and gratitude. "
مذكرة ماستر تخصص تفسير وعلوم القرآن
Keywords: أبي داود سليمان -الكهف -المؤمنون; Abi Dawid Sulayman al- kahf al- Mu'minun